2019
DOI: 10.12968/bjhc.2019.25.1.41
|View full text |Cite
|
Sign up to set email alerts
|

How do consultant radiographers contribute to imaging service delivery and leadership?

Abstract: Background: Consultant radiographer numbers remain low despite the ongoing capacity challenges in diagnostic imaging. This is compounded by the limited evidence of how such roles can positively impact on service delivery, particularly in relation to their leadership expectations. Aims: To examine the activities undertaken by consultant radiographers; evidence the impact of the roles, and consider whether the roles encompass the four domains of consultant practice. Method: Six consultant radiographers employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Exploring the enabler data by theme ( gure 3) demonstrated twelve themes with promoting advanced practice 6,13,26,38-41,45-47,49,51- 195,197,[199][200][201][202][205][206][207][208][209]211,213,214,[216][217][218][219][220][221][222][223][224][225][226][227][228][229][231][232][233][234][235][237][238][239][240]242,244,[246][247][248][249][252][253][254][255][256][257][258][259][260][262][263]…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the enabler data by theme ( gure 3) demonstrated twelve themes with promoting advanced practice 6,13,26,38-41,45-47,49,51- 195,197,[199][200][201][202][205][206][207][208][209]211,213,214,[216][217][218][219][220][221][222][223][224][225][226][227][228][229][231][232][233][234][235][237][238][239][240]242,244,[246][247][248][249][252][253][254][255][256][257][258][259][260][262][263]…”
Section: Resultsmentioning
confidence: 99%
“…Despite all advanced health care practitioners being included in the search criteria, only studies involving nurses working in advanced practice roles were identified. This may be reflective of the nursing focus on advanced practice (Thoun, 2011) but may also reflect a difficulty in broadening the scope of practice of other health care roles to advanced practice level (Snaith et al., 2019), which has resulted in a lack of clinical leadership research among non‐nursing disciplines.…”
Section: Discussionmentioning
confidence: 99%